2017
DOI: 10.17235/reed.2017.5009/2017
|View full text |Cite
|
Sign up to set email alerts
|

Colonic diverticulosis and the metabolic syndrome: an association?

Abstract: In this series, MS was significantly associated with CD. The identification of risk groups is important since diverticulosis can have serious and potentially fatal complications. To our knowledge, this is the first Southern European prospective study evaluating the association between MS and CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
1
23
0
1
Order By: Relevance
“…Patients with MS had higher complications (14% versus 5%, P < 0.01), 30-d readmissions (13% versus 6.9%, P ¼ 0.03), and mortality (8% versus 4.5%, P ¼ 0.03) compared to patients no-MS. In addition, patients with metabolic syndrome had a higher hospital length of stay (6 [4][5][6][7][8][9][10][11][12][13] d versus 10 [7-16] d, P ¼ 0.01) and were more likely to spend more than 30 d in the hospital (2.6% versus 4.7%, P ¼ 0.04) ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with MS had higher complications (14% versus 5%, P < 0.01), 30-d readmissions (13% versus 6.9%, P ¼ 0.03), and mortality (8% versus 4.5%, P ¼ 0.03) compared to patients no-MS. In addition, patients with metabolic syndrome had a higher hospital length of stay (6 [4][5][6][7][8][9][10][11][12][13] d versus 10 [7-16] d, P ¼ 0.01) and were more likely to spend more than 30 d in the hospital (2.6% versus 4.7%, P ¼ 0.04) ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…10 Multiple studies have highlighted the association between obesity/MS and colonic diverticulosis. [11][12][13] It is also well known that the presence of abdominal obesity is associated with difficulties in performing the surgical procedure as well as with worse postoperative outcomes. 14 Similarly, it has been well established in the literature that obesity leads to poor outcomes in patients with diverticulitis.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also found that IBS patients with hyperlipidaemia were more likely to develop AD than IBS patients who did not have hyperlipidaemia. It is well‐known that obesity, metabolic syndrome and nonalcoholic fatty liver disease are highly associated with the development of colonic diverticulosis [22–24]. Although these risk factors might not independently predict diverticulosis, they might be an important risk factor for the development of diverticulosis into diverticulitis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, adipocytes produce pro-inflammatory cytokines that can influence colonic motility, which promotes diverticula formation [9,20]. Studies investigating the specific role of obesity and metabolic factors in CD have shown varying results [14,19,53]. In a Southern-European prospective study, a positive association between increased waist circumference, blood pressure, hyperlipidemia, and CD was reported; also, there was no significant difference in the prevalence of T2DM and obesity between those who had CD and those who did not.…”
Section: Obesity In Nafld and Colonic Diverticulosismentioning
confidence: 99%
“…Complicated diverticular disease is diagnosed in the presence of more severe clinical conditions, such as acute diverticulitis (AD), diverticular bleeding, abscess and/or fistula development [10,11]. The role of VAT and subsequent, chronic, low-grade inflammation is important in both the pathogenesis of CD and its complications [12,13], which has led many researchers to further investigate the possible complex connection of CD and MetS [14,15]. Components of MetS, such as central obesity, dyslipidemia, and arterial hypertension (HTA), increase the risk of CDD.…”
Section: Introductionmentioning
confidence: 99%